Study of the process and problems of strategic outsourcing on-going management - Monteiro Duarte, Goncalo Nuno (Cranfield University, 2005)
Purpose To develop a model that describes the clients' management process of strategic outsourcing of services during its on-going phase. The study identifies and explores problems that occur during this phase and which influence outsourcing's effectiveness. The research studies an under-explored area and develops knowledge about the management of outsourcing during the on-going phase of continuous operation. Research design The investigation focused on strategic outsourcing - of industrial maintenance - in a single sector where such maintenance is of strategic importance, namely, in the pulp and paper industry; however, it is expected to be of value to other industries and services. The first part was exploratory, based on a single case study, and focused on the construction of the model in an inductive fashion. The second part further tested the ability of the model to describe the management of strategic outsourcing through three case studies. Findings Management of the strategic outsourcing of services consists of a number of activities which influence each other and operate concurrently at different hierarchical levels. The management process of this `stable' phase entails continuous learning and evolution. In each of the activities there are ineffective elements which originate in management problems. Such problems are identified and explored in the research and were found to originate in practices employed either by the clients or the suppliers. Research limitations/implications All case studies were conducted within one group of companies, though each company had independent management and the outsourcing was implemented differently. This approach enables the discussion about the appropriateness of the findings to describe what happens in the outsourcing of industrial maintenance in the pulp and paper industry. Moreover the research design enables the findings to have an expected value to the outsourcing of other services and in other industries. Finally, a research agenda based on the findings is suggested. It is expected to guide further exploration of the findings and to motivate the exploration of new tendencies in outsourcing practices. Practical implications The model can help outsourcing managers better understand the complexity, dynamism and problems of their own outsourcing management process, and improve their practices accordingly based on the findings. Originality/value The thesis addresses the on-going management of strategic outsourcing of services. Most literature provides insights into outsourcing strategy and high-level decisions (such as make/buy). Significant and dynamic activity and problems were seen to be occurring during this on-going phase.